Conductive CuCo‐Based Bimetal Organic Framework for Efficient Hydrogen Evolution. Issue 49 (8th October 2021) - Geng, Bo; Yan, Feng; Zhang, Xiao; He, Yuqian; Zhu, Chunling; Chou, Shu‐Lei; Zhang, Xiaoli; Chen, Yujin
Abstract: Metal–organic frameworks (MOFs) with intrinsically porous structures and well‐dispersed metal sites are promising candidates for electrocatalysis; however, the catalytic efficiencies of most MOFs are significantly limited by their impertinent adsorption/desorption energy of intermediates formed during electrocatalysis and very low electrical conductivity. Herein, Co is introduced into conductive Cu‐catecholate (Cu‐CAT) nanorod arrays directly grown on a flexible carbon cloth for hydrogen evolution reaction (HER). Electrochemical results show that the Co‐incorporated Cu‐CAT nanorod arrays only need 52 and 143 mV overpotentials to drive a current density of 10 mA cm −2 in alkaline and neutral media for HER, respectively, much lower than most of the reported non‐noble metal‐based electrocatalysts and comparable to the benchmark Pt/C electrocatalyst. Density functional theory calculations show that the introduction of Co can optimize the adsorption energy of hydrogen (Δ G H* ) of Cu sites, almost close to that of Pt (111). Furthermore, the adsorption energy of water ( Δ E H 2 O ) of Co sites in the CuCo‐CAT is significantly lower than that of Cu sites upon coupling Cu with Co, effectively accelerating the Volmer step in the HER process. The findings, synergistic effect of bimetals, open a new avenue for the rational design of highly efficient MOF‐based electrocatalysts. Abstract : Conductive bimetal‐based catecholate (CAT) nanorod arrays show excellent hydrogen evolution reaction activities in both alkaline and neutral electrolyte, comparable to that of the benchmark Pt/C. Density functional theory calculations demonstrate that the incorporation of Co not only optimizes the Δ G H* and the adsorption energy of water ( Δ E H 2 O ) of Cu‐CAT, but also increases the electrical conductivity of Cu‐CAT.